The social (de-)construction of the Corona-pandemic as being a serious threat to society: Insights from a discourse analysis of German tweets until contacts were banned in March 2020 - Jana Deisner; Johanna Mai; Carolin Auschra (Freie Universität Berlin, School of Business & Economics, 2021)
This essay examines how different individual and collective actors interpreted the initial weeks of the worldwide COVID-19 outbreak from the German perspective. During this early phase, knowledge about COVID-19 was quite limited and uncertain, which also influenced the ability to assess (potential) impacts. The analysis relies on twitter data and traces the main arguments in the public German discourse between January and March 2020. It shows that actors ascribed different meanings to the outbreak - either recognizing or negating the gravity of the COVID-19 threat. Shortly before the first German lockdown, the seriousness of the COVID-19 threat had begun to feature prominently within the public discourse.
urn:nbn:de:kobv:188-refubium-29627-3; hdl:10.17169/refubium-29371
Keywords: 650; Pandemic; COVID-19; social construction; discourse analysis; Twitter